Detection of Neonectria fuckeliana in Chile associated to stem cankers and malformations in Pinus radiata plantations - Morales R., Rodrigo (BOSQUE, 2009)
The presence of the fungus Neonectria fuckeliana in Pinus radiata plantations in the commune of Toltén, Region of Araucanía, Chile was reported. The presence of cankers and kink-stem of the trees were observed as symptoms of infection which started from the areas of healing of pruning. About 80% of the trees in the stands surveyed presented damage. On the bark of the cankered stems, we observed abundant fruiting bodies growing in a clumped pattern presenting spherical forms and a reddish brown color; which were analyzed in the laboratory. According to microscopy and taxonomic keys of these structures, we found that they agreed with the perithecia N. fuckeliana; the disease characterized by producing stem cankers and malformations on stems, such as those described in coniferous species. The present study is the first report of damage caused by N. fuckeliana in P. radiata plantations in the country, thus starting studies to address this problem arises as urgent.